2014
DOI: 10.3390/molecules191219980
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative Effects of Siegesbeckia orientalis Ethanol Extract on Human Endometrial RL-95 Cancer Cells

Abstract: Endometrial cancer is a common malignancy of the female genital tract. This study demonstrates that Siegesbeckia orientalis ethanol extract (SOE) significantly inhibited the proliferation of RL95-2 human endometrial cancer cells. Treating RL95-2 cells with SOE caused cell arrest in the G2/M phase and induced apoptosis of RL95-2 cells by up-regulating Bad, Bak and Bax protein expression and down-regulation of Bcl-2 and Bcl-xL protein expression. Treatment with SOE increased protein expression of caspase-3, -8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 34 publications
0
27
1
Order By: Relevance
“…A recent study [24] showed that SO ethanol extract significantly inhibited the proliferation of RL 95-2 human endometrial cancer cells. Furthermore, SO ethanol extract was effective against A549 (lung cancer), HepG2 (hepatpma), MDA-MB-231 (breast cancer), and especially on LNCaP (prostate cancer) cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study [24] showed that SO ethanol extract significantly inhibited the proliferation of RL 95-2 human endometrial cancer cells. Furthermore, SO ethanol extract was effective against A549 (lung cancer), HepG2 (hepatpma), MDA-MB-231 (breast cancer), and especially on LNCaP (prostate cancer) cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that (−)-guaiol possesses significant cytotoxicity on NSCLC cells and regulates autophagic cell death [49,50]. β-Caryophyllene, an important component in the extracts of various species of medicinal plants, has been reported to have anti-proliferative effects on various cancer cells, including pancreatic cancer, colon cancer [51], hepatoma [52], endometrial cancer [53], and skin epidermoid cancer [54].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, other studies have mentioned that citrals were apoptotic against chronic lymphoid leukemia by activation of caspase-3. [15] In addition, other authors showed that b-elemene inhibits the proliferation of human glioblastoma cells through the activation of glia maturation factor b and induces sensitization to cisplatin. [15] In addition, other authors showed that b-elemene inhibits the proliferation of human glioblastoma cells through the activation of glia maturation factor b and induces sensitization to cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…[14] In the same idea, caryophyllene oxide has been reported to be responsible for a cytotoxic activity against RL95-2 cells of endometrial cancer. [15] In addition, other authors showed that b-elemene inhibits the proliferation of human glioblastoma cells through the activation of glia maturation factor b and induces sensitization to cisplatin. [16] A high cytotoxic activity of b-elemene on MCF7 tumor cells with IC 50 = 14.70 lg/ml was also reported by Chen et al [17] These results also corroborate those reporting that limonene is an inhibitor of tumor progression by acting on the protein P21ras.…”
Section: Resultsmentioning
confidence: 99%